2011
DOI: 10.1097/prs.0b013e31821b6336
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Minimally Invasive versus Conventional Open Harvesting Techniques for Iliac Bone Graft in Secondary Alveolar Cleft Patients

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 27 publications
0
58
0
Order By: Relevance
“…2 Historically, these iliac bone grafts have been obtained by an open approach (approximately 3-4-cm incision to obtain adequate visualization, blunt dissection down to iliac crest, and harvesting of bone by means of an osteotome) described by Lindeman in 1915 and popularized by Wolfe and Kawamoto. 3,4 Recently, iliac bone grafts have been obtained by minimally invasive techniques (closed approach) using different surgical devices such as percutaneous needle, Volkmann curette, modified bone core biopsy trocar, cylinder osteotomes, manually driven osteotome, motorized CORB needle, bone grinder, grinding harvester, and mechanized coring, among others. 1,3,[5][6][7] In this context, as iliac crest bone grafting has been associated with numerous donor site morbidities, especially donor site pain (a potential source of anxiety, fear, and stress for both patients and family members 8 ), many investigations 3,5,6,9 -13 have been carried out comparing pros and cons between the conventional open techniques and closed minimally invasive techniques for iliac bone graft harvesting.…”
mentioning
confidence: 99%
“…2 Historically, these iliac bone grafts have been obtained by an open approach (approximately 3-4-cm incision to obtain adequate visualization, blunt dissection down to iliac crest, and harvesting of bone by means of an osteotome) described by Lindeman in 1915 and popularized by Wolfe and Kawamoto. 3,4 Recently, iliac bone grafts have been obtained by minimally invasive techniques (closed approach) using different surgical devices such as percutaneous needle, Volkmann curette, modified bone core biopsy trocar, cylinder osteotomes, manually driven osteotome, motorized CORB needle, bone grinder, grinding harvester, and mechanized coring, among others. 1,3,[5][6][7] In this context, as iliac crest bone grafting has been associated with numerous donor site morbidities, especially donor site pain (a potential source of anxiety, fear, and stress for both patients and family members 8 ), many investigations 3,5,6,9 -13 have been carried out comparing pros and cons between the conventional open techniques and closed minimally invasive techniques for iliac bone graft harvesting.…”
mentioning
confidence: 99%
“…This is consistent with prior studies that have reported the iliac crest to be most popular bone graft source. 10,22 Approximately 2% had bone from the femur, tibia, or ribs. None of the patients had bone grafts from the cranial bones.…”
Section: Discussionmentioning
confidence: 99%
“…16 Meanwhile, such complications are clearly lower in patients receiving maxillofacial surgery if no structural bone grafts are needed and thus the minimally invasive harvesting techniques can be employed. 11 If we consider the continuous increase in publications addressing this subject in recent years 10 and the fact that 2 years after harvesting bone from the iliac crest, up to 31% of patients still suffer pain, 17,18 then the conclusion is likely that an ideal operation technique for harvesting bone grafts with defined demands on graft size and quality does not yet exist.…”
Section: Discussionmentioning
confidence: 99%
“…10 For many indications, however, for which the bone graft must be of a minimal size or of a certain structural quality (corticocancellous bone graft), it is not possible to utilize the minimally invasive tools of maxillofacial surgery. 11 In our ward, apart from the classical harvesting of a corticocancellous bone graft by means of an oscillating saw, 12 for graft harvesting, we are increasingly utilizing a new, manual iliac crest reamer (Gebrüder Martin GmbH & Co. KG, Tuttlingen, Germany). With this tool, it is possible to obtain bicortical bone cylinders with a radius of 16 mm or 20 mm for a great number of indications.…”
mentioning
confidence: 99%